2017
DOI: 10.1111/wvn.12213
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress in Nurses Providing Direct Patient Care at an Academic Medical Center

Abstract: Three variables were found useful in predicting moral distress: the type of unit and responses to two qualitative questions related to quitting their job. Identification of these variables allows organizations to focus their interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…Nurses employed in Mental Health Services (MHN) may encounter a series of ethical issues and related problems, which may lead to morally distressing experiences [ 43 , 44 ]. Moral distress is a phenomenon of increasing concern in mental health nursing practice, education, and research due to the increased frequency of ethically and morally charged situations in mental healthcare settings compared to other clinical contexts [ 22 , 45 , 46 ]. The psychopathological changes in people suffering from mental illness may undermine their capacity to consent treatment procedures [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses employed in Mental Health Services (MHN) may encounter a series of ethical issues and related problems, which may lead to morally distressing experiences [ 43 , 44 ]. Moral distress is a phenomenon of increasing concern in mental health nursing practice, education, and research due to the increased frequency of ethically and morally charged situations in mental healthcare settings compared to other clinical contexts [ 22 , 45 , 46 ]. The psychopathological changes in people suffering from mental illness may undermine their capacity to consent treatment procedures [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…1a). Compared with third and fourth year students, second year students reported lower median (IQR) composite moral distress scores (8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] versus 30 and 29 ) and a lower prevalence of burnout (28% versus 48 and 40%). While there was less moral distress and burnout among second year students who had overall less clinical experience, the Rotation experienced on which scenario most commonly experienced b Percentages do not add to 100% because the choices were not mutually exclusive association between moral distress score and burnout did not appear to vary by medical school year (p-forinteraction = 0.62, see Supplement Table 4).…”
Section: Burnoutmentioning
confidence: 99%
“…Among nurses, resident physicians, and attending physicians, moral distress is associated with decreased professional quality-of-life and burnout [8][9][10][11][12][13][14][15][16][17][18][19][20], and burnout is associated with poor mental health and lower quality of patient care [21]. The association between moral distress and burnout has not yet been studied in medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to our study, Silen et al (2011) identified low frequency with moderate intensity; with an attendant explanation that a more positive ethical climate correlated with a lower frequency of moral distress. Whilst there is complementarity here between all three studies, we do recognise variations across different types of clinical units have been identified by others (Sirilla, Thompson, Yamokoski, Risser, & Chipps, 2017).…”
Section: Phase 1: Measuring Moral Distressmentioning
confidence: 54%
“…Differences such as this in the appearance of moral distress across clinical contexts, are evident in the literature (Burston & Tuckett, 2013;Sirilla et al, 2017 This finding interprets in three ways: (1) these situations do not occur frequently within the aged care workforce, (2) the results are an aberration and not truly representative of the broader aged care workforce, or (3) they occur infrequently in this specific population (that is the context or environment this population operates within). For the first two points noted further exploration with larger samples will provide clarity.…”
Section: Phase 1: Measuring Moral Distressmentioning
confidence: 85%